Clinico-Demographic Profile and Pregnancy Outcome in Placenta Previa: A Study from Tertiary Care Hospital - Haque, Husneyara; Pandit, Upendra (Journal of Nepalgunj Medical College, 2017)
Introduction: Placenta previa is an obstetric complication which causes considerable maternal and fetal morbidity and mortality during pregnancy. This study is done with the objective to find out the clinico-demographic factors associated with placenta previa and to analyze maternal and perinatal outcome in these cases. Methods: This was a retrospective study done in the department of Obstetrics and Gynecology of Nepalgunj Medical College Teaching Hospital, Nepalgunj, a tertiary care hospital from Midwestern Nepal. Relevant data were retrieved from maternity register from June 2015 to May 2017. All women who had undergone caesarean section for placenta previa were included in this study. Result: Out of total 5812 deliveries during the study period there were 50 caesarian sections done for placenta previa which is 0.86% of total deliveries. Maximum number of mothers belonged to 26- 30 years of age group. Commonest type of placenta previa was minor type. About 72% were multiparous. 20% had previous LSCS and 24% had previous abortion. Postpartum hemorrhage was present in 36% mothers and 32% received blood transfusion. About 64% new born were preterm and low birth weight. 34% babies had less than 7 apgar score at 5 min. Still births were 6%. Conclusion: Placenta previa poses greater risk and need of blood transfusion to mother as well as birth of preterm and low birth weight babies which leads to perinatal morbidity and mortality. Timely diagnosis, regular antenatal check up and effective management may improve pregnancy outcome.